The period of immobilisme Philippine foreign relations during the administrations of Carlos P. Garcia and Diosdado P. Macapagal, 1957-1965 - Madrona, Severo Cañete Jr (Central Books Supply, 2021)
This book is written to provide an in-depth study of the key factors that paved the way for the shift in the Philippine foreign policy orientation from 1957 to 1965. It presents a case study in the formulation and implementation of Philippine foreign policy. It examines the factors and reasons on how and why the foreign policies of the Philippines during the period of immobilisme were formulated and implemented from 1957 to 1965. By Using the ecological perspective in foreign policy analysis, this study examines the milieu of the period resulting in the formulation and implementation of foreign policies by Presidents Carlos P. Garcia and Diosdado P. Macapagal. The empirical evidence suggests that while Garcia and Macapagal’s foreign policies were responsive to the milieu, the desired outcomes were not achieved as the personnel implementing the foreign policies had failed to make the policies understood by the international community and the Filipino people.